Effects Of Environmental Performance On Firm Value With The Mediation Of Csr Disclosure (A Study on Mining Companies Listed on the Indonesia Stock Exchange in the 2020–2023 Period) - Caesario, Yulian Lega; Nugraha, Adri Putra (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study examines the effect of environmental performance on firm value, with CSR disclosure as a mediating variable. From all mining companies listed on the IDX during the 2020–2023 period, 48 companies were selected as samples using a purposive sampling technique. Data analysis using Partial Least Squares (PLS) reveals that environmental performance does not directly affect firm value but does so indirectly through CSR disclosure. This finding empirically supports stakeholder theory and legitimacy theory, particularly regarding the role of CSR disclosure in mediating the relationship between environmental performance and firm value. The study provides insights for mining companies, emphasizing that both environmental performance and CSR disclosure contribute positively to firm value.